MORAL MESSAGE IN THE NOVEL “THIRTEEN REASONS WHY” BY JAY ASHER (Karya Ilmiah Mahasiswa (KIMA), 2024)
A moral message can also be interpreted as a message in a work that the author wants to convey to the reader. The presence of a moral message in a novel indicates that the story is intended to benefit the reader as well as to entertain the reader. Moral messages serve as role models and examples for readers. The purpose of this study is to explain the moral message of Jay Asher's novel “Thirteen Reasons Why” and its impact on teens. The research method used in this study is a descriptive qualitative method. The data source used in this study is Jay Asher's novel “Thirteen Reasons Why”. The study found that Jay Asher's novel “Thirteen Reasons Why” contains 18 moral messages, and that there are 7 moral messages that can influence teens.